Pengaruh Variasi Perendaman Terhadap Kadar Hidrogen Sianida (HCN) Pada Keripik Kulit Singkong (Manihot esculenta) - Ahmad Mundzir Romdhani; Ulfa Maulida Farid; Istiqamatul Jannah (Institut Agama Islam Negeri Kerinci, 2025)
Cassava skin contains toxic compounds that can poison the body if consumed. These dangerous compounds are hydrogen cyanide (HCN). The appropriate cassava skin processing process can trigger a decrease in cyanide levels. As with the processing of cassava skin into delicious cassava skin chips. The purpose of this study was to determine the effect of soaking variations on hydrogen cyanide (HCN) levels in cassava skin chips (Manihot esculenta). This type of research is a quantitative experiment. The research method used is steam distillation and titration tests. The selection of cassava skin samples used a simple random sampling technique. This study had 3 treatments including, P1: soaking with water, P2: soaking with salt water, P3: soaking with lime water. Each treatment was repeated 6 times. The data analysis technique used was a single variance analysis (one way anova) with a significance level of 0.05. The results of the study showed that there was a significant effect of soaking variation treatment on hydrogen cyanide (HCN) levels in cassava skin chips with a Sig. value of 0.000. The treatment of soaking in lime water for 7 days has proven effective in reducing cyanide levels by 99.67%.